Organizational culture and Nitaqat status in Saudi Arabia - Alanazi, Amer; Mohd Shamsudin, Faridahwati; Johari, Johanim (2014)
The Nitaqat program is the latest in the Saudization policies to increase the number of Saudi workforce in the local labor market and to reduce the heavy reliance on foreign labors in the Kingdom of Saudi Arabia.We argue that hiring decisions made by private sector organizations are not entirely based on government mandates alone. We propose that the internal organizational characteristics are also important in determining the hiring decision. Applying resource-based view, we demonstrate how organizational culture, leadership style, and human resource management practices could play a key role toward such decision and hence the Nitaqat status.